Modeling seismic wave propagation in partially saturated porous media: a comparative study - Chen, Weishi; Zhang, Xingjie; Dai, Tian xing; Peng, Junjie; Ni, Zhiwei (Frontiers in Earth Science, 2025)
Seismic wave propagation in partially saturated porous media involves multiscale wave-induced fluid flow (WIFF) mechanisms, which significantly impact distinct wave dispersion and attenuation across different frequency bands. It is well known that WIFF at different scales leads to distinct characteristics of wave dispersion and attenuation. Therefore, accurately modeling multiscale WIFF over a wide frequency range is crucial for reservoir characterization and geophysical interpretation based on multiscale measurements. In this study, we integrate the stable effective fluid (SEF) model with squirt flow (SQ) mechanism dominated by microscopic compressibility, developing and validating two multiscale wave propagation models, SEF-SQ and Biot-SQ, by integrating the stable effective fluid and squirt flow mechanisms into existing theoretical frameworks. This model is capable of describing the wave propagation in the porous medium containing two immiscible fluids over a broadband frequency range. Moreover, we incorporate the microscopic WIFF mechanism into the classical macroscopic Biot’s theory through certain characteristic parameters, formulating the Biot-SQ model, which couples global and local wave propagation mechanisms. Numerical simulations demonstrate that both SEF-SQ and Biot-SQ models successfully capture wave dispersion and attenuation characteristics across different frequency bands, confirming their capability to describe the wave propagation over a broadband frequency range. Furthermore, we implement a GPU-based numerical method to efficiently solve the two developed integrated multiscale wave equation systems, and compare the simulated seismic wavefields under different physical parameters, verifying the applicability of this multiscale framework for seismic wavefield modeling. The results emphasize the influence of fluid saturation on WIFF mechanisms in complex porous media, providing valuable insights for reservoir characterization and hydrocarbon exploration.